Pengaruh Variasi Produk dan Kualitas Layanan terhadap Kepuasan Konsumen pada Kedai Kopi Tilik Sawah Kota Kediri - Devi Wulan Margaretha; Angga Rizka Lidiawan; Dita Riyanto Putro (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to examine the influence of product variation and service quality on consumer satisfaction at Kedai Kopi Tilik Sawah in Kediri City. The growth of the coffee shop industry in Indonesia, including in Kediri City, shows a positive trend along with the increasing interest of the public, especially young people and workers, who use coffee shops as places to relax, study, and work. Kedai Kopi Tilik Sawah has become a popular destination due to its open concept and natural, comfortable atmosphere. The research method used is a quantitative approach by distributing questionnaires to 100 respondents selected through purposive sampling. The data were analyzed using multiple linear regression with SPSS version 25 software. The results show that product variation and service quality have a positive and significant effect on consumer satisfaction, both partially and simultaneously. These findings emphasize the importance of managing diverse products and quality services in building customer loyalty. The implications of this study can serve as a reference for coffee shop managers in designing more effective marketing strategies to face the increasingly competitive local culinary industry.